The kiss quotient eaudiobook - Hoang, Helen (Kiss Quotient, 2018)
Stella Lane thinks math is the only thing that unites the universe. She comes up with algorithms to predict customer purchases—a job that has given her more money than she knows what to do with as well as way less experience in the dating department than the average thirty-year-old. It doesn't help that she has Asperger's and that French kissing reminds her of a shark getting its teeth cleaned by pilot fish. She decides that she needs lots of practice—with a professional—which is why she hires escort Michael Phan. The Vietnamese-Swedish stunner can't afford to turn down Stella's offer, and he agrees to help her check off all the boxes on her lesson plan—from foreplay to more-than-missionary position... Before long, Stella not only learns to appreciate his kisses but also to crave all of the other things he's making her feel. Their no-nonsense partnership starts making a strange kind of sense. And the pattern that emerges convinces Stella that love is the best kind of logic.